Functional assessment of motor patterns in fitness practice of mature individuals - Vypasniak, Ihor; Fedyniak , Nazarii (Journal of Education, Health and Sport, 2024)
Relevance. In the context of health improvement strategies for the adult population, the implementation of innovative technologies is a prerequisite for the introduction of advanced scientific ideas. Research shows that the assessment of functional parameters of movements is a determining criterion for the effectiveness of preventive health programs aimed at ensuring comprehensive physical development and improving physical fitness. Research tasks. Systematization of data obtained by Ukrainian scientists on the development of physical qualities in mature individuals. In the methodological aspect, the Functional Movement Screen (FMS) system was used by specialists for an objective functional assessment of movements. Research results. The relevance of modern health fitness practice determines the critical need for the development and implementation of specialized screening methods using a functional approach for the preventive detection of motor deficits. In this context, FMS is considered as a potential method for determining objective markers of the basic level of motor competence. FMS is a standardized system for assessing the quality of motor patterns and screening motor competence in uninjured individuals. The system uses a simple ordinal scale that allows for the rapid identification of potential functional limitations and asymmetries. It is important to note that FMS is not a diagnostic tool and is not intended to detect pathologies. Its main goal is to identify functional limitations and dysfunctions in relatively healthy individuals, which allows for the implementation of proactive injury prevention strategies. This approach allows for a timely response to potential risks, helping to maintain optimal motor health and reduce the incidence of injuries. Conclusions. In the current scientific discourse, it is emphasized that in the conditions of hypodynamia, which is a characteristic feature of the modern lifestyle, the importance of physical exercise increases significantly. Its use is considered a fundamental prerequisite for maintaining and strengthening health, as well as for achieving harmonious physical development of the individual. Screening of movements based on the analysis of fundamental movement patterns is a key tool for identifying hidden deficits in mobility and stability in asymptomatic but physically active populations. These functional limitations are often not detected by standard testing methods that focus on diagnosing existing disorders.